PERUBAHAN LAPANGAN PEKERJAAN DARI PERTANIAN KE PERTAMBANGAN ( STUDI KASUS PERTAMBANGAN EMAS TANPA IZIN DI DESA TANAH BEKALI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI ) - Indri Cahyani Putri; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research discusses the change in employment from agriculture to mining in Tanah Bekali Village, Pangean District, Kuantan Singingi Regency. This research was motivated by rubber plantations, rice fields that were used as unlicensed gold mining (PETI) so that there was a transfer of land from agriculture to mining as well as changes in people's livelihoods, and caused consumptive behavior. Peti's activities are illegal as well as a risk to people's lives that will come, due to the depletion of gold content. The reason people make their land a mining location is because of the fall in rubber prices, while agriculture, especially rubber plantations, is the community's mainstay source of income. This research is carried out using qualitative research methods. The selection of informants in this study used purposive sampling techniques. Data types are primary data and secondary data. The method of data collection is carried out in three ways: observation, interviews and documentation. The results of research after the change in employment from agriculture to mining is that the socio-economic community increases with evidence that people can build permanent homes and buy vehicles. And its survival can be fulfilled every day compared to before becoming a rubber farmer.Keywords: Socio - economic, Miner, Job Change